PROPOSED AGGREGATE SCHEDULING MODEL OF ENGINEER-TO-ORDER (ETO) PRODUCTION SYSTEM AT PT ARINDO CIPTA PERKASA - Ilham Falah, Ahmad
PT Arindo Cipta Perkasa (ACP) is a company engaged in manufacturing. PT ACP produces various kitchen appliance products made of stainless steel. PT ACP implements an engineer-to-order (ETO) production system, where customers can request certain specifications of the ordered product. In completing the order, PT ACP has three considerations, namely product quality, product price, and delivery time. As a company that implements the ETO production system, timeliness of completion is an important criterion for customer satisfaction to be maintained. Currently PT ACP does not have an appropriate scheduling method, where details of the production process are scheduled daily by the Production Manager. If multiple orders are entered simultaneously, then the level of scheduling difficulties increases because it is necessary to divide the limited capacity to complete the projects. Currently, PT ACP does not implement overtime and subcontracting hours so delays can occur if capacity is not enough to work on incoming projects. This research aims to develop an engineer-to-order (ETO) production system aggregate scheduling model at PT ACP. The developed model is an analytic model based on linear programming and has the objective function of minimizing the total tardiness that occurs on each scheduled project. The model computing process is performed using IBM ILOG CPLEX Optimization Studio 20.1.0 software. The development model test was conducted using historical data on project work at PT ACP on November 20, 2020 - January 13, 2021. There are 11 projects scheduled with two scheduling periods. The computational results of the development model provide a total tardiness value of 49 days and a maximum completion time (makespan) of 21 days.